Global linkages across sectors and frequency bands: a band spectral panel regression approach - Jingjing Lyu; Bernd Süssmuth (Review of World Economics, 2025)
We introduce the technique of band spectral panel regression (BSPR) to analyze global linkages across sectors and frequency bands. It relies on decomposing time series—allowably measured in mixed observation frequency—into "deviation cycle" dynamics by frequency band. We use it to compute measures of real co-movement, trade linkage, financial market integration, and policy coordination band by band. Considering intra-industry as well as inter-industry linkage indicators, we apply it to data of contemporary China and 22 of its top-25 major trading partners in the pre-trade war and pre-pandemic era. Band-specific fixed effects and band-industry-specific interaction terms are included. For labor intensive industries co-movement through intra-industry trade linkages is found to be band-specific. Moreover, our results clarify the puzzle of financial globalization implying real regionalization or contagious synchronization of cyclical dynamics. We find the latter to hold in the 4–6 years band and the former in the 6–10 years range.
Keywords: C32; C49; E32; F40; 330; Spectral regression; Frequency domain; Cyclical co-movement; Sectors